2019
DOI: 10.21109/kesmas.v14i2.2774
|View full text |Cite
|
Sign up to set email alerts
|

Midwife’s Role in the Mother-to-Child Transmission Prevention Program in Primary Health Care in Yogyakarta

Abstract: Curing and eradicating Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) are to the core principles of the United Nations’ Sustainable Development Goals (SDGs). The incidence of HIV in the world remains high. Although midwives play a pivotal role in PMTCT implementation, the factors associated with midwives’ role in its implementation are not well understood. The aim of this study was to determine factors associated with midwives’ role in implementation of PMTCT. This study used a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…A study in Yogyakarta found that social support from the midwife can improve the utilization of PMTCT services. 27 Other studies also found that social support from peer support groups and health providers can reduce the impact of stigma and discrimination, which increases the confidence of women living with HIV in accessing PMTCT services. 28,29 Meanwhile, this study found that perceived severity increases the likelihood of women living with HIV accessing the PMTCT for HIV, Syphilis, and Hepatitis B.…”
Section: Discussionmentioning
confidence: 98%
“…A study in Yogyakarta found that social support from the midwife can improve the utilization of PMTCT services. 27 Other studies also found that social support from peer support groups and health providers can reduce the impact of stigma and discrimination, which increases the confidence of women living with HIV in accessing PMTCT services. 28,29 Meanwhile, this study found that perceived severity increases the likelihood of women living with HIV accessing the PMTCT for HIV, Syphilis, and Hepatitis B.…”
Section: Discussionmentioning
confidence: 98%
“…A study mentions that intervention in the form of standardized knowledge sharing and contact with people living with HIV for 50 minutes with health workers in Hong Kong can reduce the stigma among health workers [23]. The provision of HIV education, testing, and messages such as brochures, bulletins, and testimony can reduce stigma [6,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, midwives would play an important role as health educators and promotors to encourage the mother to do HIV tests. However, many midwives lack knowledge and attitudes toward sexuality and HIV/AIDS [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Yogyakarta, for example, it was found that the role of midwives was in the good category in PMTCT, but the respondents were taken from midwives practicing at the PHCs only and not based on the role of each of the prong. 15 The assessment of the midwives role was not differentiated between those who have served HIV-positive patients (did all prong) and who have never served HIV-positive patients (only did PMTCT prong 1). Study in South Africa in 2016, found that the implementation of…”
Section: Discussionmentioning
confidence: 99%